Exploring the effects of moxibustion on cognitive function in rats with multiple cerebral infarctions from the perspective of glial vascular unit repairing - Wang, Jingji; Du, Kunrui; Liu, Chang; Chen, Xiaoyu; Ban, Wenming; Zhu, Guoqi; Yang, Jun (Frontiers in Pharmacology, 2024)
Objective: This study aimed to explore the effect of moxibustion at Governor Vessel (GV) acupoints, including Baihui (GV 20), Shenting (GV 24) and Dazhui (GV 14) for 14 days on glial vascular unit (GVU) in rats with multiple microinfarctions (MMI), and to explore its action mechanism.Methods: The effect and mechanism of moxibustion on vascular dementia (VD) were studied in MMI rats by means of behavioral and molecular biology experiments.Results: Rats receiving MMI showed impairment of memory function, reduction of cerebral blood flow, damage of blood-brain barrier (BBB) integrity and increased brain mass. MMI also increased neuronal degeneration in the hippocampus. Notably, levels of glial fibrillary acidic protein (GFAP) and complement component 3 significantly increased, but those of Connexin43 (CX43) and platelet derived growth factor receptor β (PDGFRβ) significantly decreased in the hippocampus of the rats receiving MMI. Moxibustion, as well as oxiracetam (ORC) treatment improved memory function and neuronal degeneration, ameliorated BBB integrity, increased cerebral blood flow and decreased brain mass. In addition, moxibustion as well as oxiracetam (ORC) treatment reduced the decrease of CX43 protein and increased PDGFRβ protein level in the hippocampus of MMI rats. Moreover, moxibustion treatment reversed MMI-induced increase of the GFAP/CX43 ratio in vascular structural units. Importantly, after PDGFRβ inhibition, VD rats treated with moxibustion had impaired learning and memory, decreased cerebral blood flow, and BBB disruption.Conclusions: Moxibustion treatment at various GV acupoints improved cerebral blood flow and repaired BBB function in rats with MMI, likely through protecting GVU.